Partially Oxidized Alginate as a Biodegradable Carrier for Glucose‐Responsive Insulin Delivery and Islet Cell Replacement Therapy. Issue 2 (9th November 2022) - Volpatti, Lisa R.; Bochenek, Matthew A.; Facklam, Amanda L.; Burns, Delaney M.; MacIsaac, Corina; Morgart, Alexander; Walters, Benjamin; Langer, Robert; Anderson, Daniel G.
Abstract: Self‐regulated insulin delivery that mimics native pancreas function has been a long‐term goal for diabetes therapies. Two approaches towards this goal are glucose‐responsive insulin delivery and islet cell transplantation therapy. Here, biodegradable, partially oxidized alginate carriers for glucose‐responsive nanoparticles or islet cells are developed. Material composition and formulation are tuned in each of these contexts to enable glycemic control in diabetic mice. For injectable, glucose‐responsive insulin delivery, 0.5 mm 2.5% oxidized alginate microgels facilitate repeat dosing and consistently provide 10 days of glycemic control. For islet cell transplantation, 1.5 mm capsules comprised of a blend of unoxidized and 2.5% oxidized alginate maintain cell viability and glycemic control over a period of more than 2 months while reducing the volume of nondegradable material implanted. These data show the potential of these biodegradable carriers for controlled drug and cell delivery for the treatment of diabetes with limited material accumulation in the event of multiple doses. Abstract : Partially oxidized alginate is used to provide biodegradable carriers for self‐regulated diabetes therapies. Material composition and formulation is tuned to encapsulate and deliver glucose‐responsive, insulin‐loaded nanoparticles or insulin‐secreting pancreatic islet cells. Diabetic animals receiving these therapies experience glycemic control with minimal accumulation of material over time.